Performance evaluation of heterostructured tungsten disulfide/tungsten diselenide for corrosion inhibition on diverse metal substrates - M. Ananthkumar; Saravanakumar Tamilarasan; K. M. Mini (Discover Applied Sciences)
Abstract The development of advanced materials with multifunctional properties is crucial for addressing corrosion challenges in modern engineering applications. In this work, a novel approach to corrosion inhibition using solid lubricants based on tungsten dichalcogenides such as Tungsten disulfide (WS₂), Tungsten diselenide (WSe₂), and Tungsten disulfide—Tungsten diselenide heterostructures (WS₂/WSe₂) is presented. The WS₂/WSe₂ heterostructure, synthesized via a one-pot solvothermal method, exhibits a unique crystalline structure and enhanced mechanical stability, making it a promising candidate for dual applications in wear protection and corrosion inhibition. Characterization techniques such as XRD, SEM with EDAX, and AFM confirmed the structural integrity and surface morphology of the synthesized materials. The doctor’s blade method was employed to fabricate defect-minimized coatings on Magnesium (Mg), Copper (Cu), and Stainless Steel (SSL) substrates. Corrosion inhibition performance was systematically evaluated using potentiodynamic polarization and electrochemical impedance spectroscopy in a 3.5% NaCl solution. Compared to the individual dichalcogenides, the WS₂/WSe₂ heterostructure demonstrated superior corrosion resistance, achieving inhibition efficiencies of 79.3% for Cu, 50.1% for Mg, and 52.6% for SSL. The corresponding icorr values were 711.4, 558, and 768 μA/cm2, with corrosion rates of 3.24 × 10⁻5, 5 × 10⁻5, and 2.73 × 10⁻5 mpy for Cu, Mg, and SSL substrates, respectively. These findings establish the WS₂/WSe₂ heterostructure as a highly effective material for next-generation anticorrosion technologies.